TINJAUAN ESTETIKA ROTAN DAN ECENG GONDOK PADA PRODUKSI KURSI DI DESA TRANGSAN - Nurohman, Nurohman; Triyono, Triyono (Universitas Telkom, 2021)
Trangsan Village in Gatak, Sukoharjo Regency, Central Java Province has been the center of the rattan handicraft industry since 1927. Currently it is the largest rattan industry in Central Java. Rattan raw materials imported from Kalimantan and then processed into ready-to-use goods for household needs. The policy to export raw rattan again in order to reduce the level of smuggling makes raw materials difficult to obtain. So that the Trangsan village craftsmen creatively combine materials from water hyacinth to reduce the use of rattan. This creativity is a source of research ideas regarding the aesthetics of combining rattan and water hyacinth materials as the manufacture of chair products. Descriptive qualitative research will describe the findings of applications with aesthetic value and quality. Data collection techniques using observation and interviews, as well as documentation. Data analysis found the conclusion that the aesthetic value of the chairs produced by Trangsan comes from the harmony of the woven layout which creates a sense of pleasure and satisfaction from its customers. Keywords: Rattan and Water Hyacinth, Aesthetic value, Stool products